PENGARUH PERGANTIAN MANAJEMEN, PERTUMBUHAN PERUSAHAAN, FINANCIAL DISTRESS, REPUTASI AUDITOR, NILAI PERUSAHAAN DAN PROFITABILITAS TERHADAP AUDITOR SWITCHING PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2020- 2022 - Riansyah, Rhonny; Elvisa, Sonia (Jurnal Akuntansi Kompetif, 2024)
The purpose of this study is to examine the impact of independent variables (management turnover, company growth, financial distress, auditor reputation, firm value, and profitability) on the dependent variable (auditor switching). This research utilized a sample of manufacturing companies listed on idx.co.id during the period from 2020 to 2022. The sample comprised 31 manufacturing companies, observed over three years. Using purposive sampling method, the total sample for this study consisted of 93 financial statements. Hypothesis testing was conducted using logistic regression analysis. The findings indicate that management turnover has a positive and significant effect on auditor switching. Company growth, financial distress, and profitability showed a positive but not significant influence on auditor switching. Meanwhile, auditor reputation and price to book value had an insignificant negative impact on auditor switching Keywords: Auditor switching, profitability, firm value, reputation, financial distress, company growth, manajemen change.